T69. PATHWAYS TO CARE ENCOUNTERS AND DURATION OF UNTREATED PSYCHOSIS IN MINORITY ETHNIC PATIENTS AT FIRST EPISODE OF PSYCHOSIS: A MENTAL HEALTH ELECTRONIC CASE REGISTER STUDY. (9th April 2019) - Oduola, Sheri; Craig, Tom; Morgan, Craig
Abstract: Background: Duration of untreated psychosis (DUP) is identified as a major contributor to the variation in outcomes following first episode psychosis. We investigated to what extent differences in pathways to care and DUP by ethnicity is associated with the type of specialist mental health service the patients encounter during first contact with mental health services. Methods: We analysed data on 343 first episode psychosis patients presenting to the South London and Maudsley NHS Trust, who were eligible to receive early intervention (EI) for psychosis between 2010 and 2012. We performed crude and multivariable logistic regression to estimate odds of DUP by pathways to care characteristics and ethnic groups, controlling for confounders. Results: We found around thirty-five percent of the sample did not receive an early intervention for psychosis. Among the EI patients, a short DUP was strongly associated with demographic factors and pathways encounters. When EI and non-EI patients were compared, both experienced longer DUP if they were referred by GP (OR=2.30; 95%CI=1.30 – 1.07) and (OR=2.65; 95%CI=1.13 – 6.06) respectively. There was strong evidence that black Caribbean patients in the EI group experienced shorter DUP compared with white British patients (adj. OR=0.33; 95%CI=0.11 – 0.98), independent of confounders. Discussion: Our findings show that ethnicity is associated duration of untreated psychosis, and black Caribbean patients, experienced shorter DUP. Longer DUP was associated with GP referral, which may reflect the ongoing pressures on resources and waiting times for consultation in primary care.